Strength and weakness of the National Nutrition Improvement Program in Rural and Nomadic Women: findings from a policy triangle framework - Kalantari, Naser; Abdollahi, Morteza; Amiri, Parisa; Zayeri, Farid; Ezzeddin, Neda (Frontiers in Sustainable Food Systems, 2023)
Introduction Nutrition-sensitive agriculture (NSA) is a comprehensive, inter-sectoral approach to improve food security and nutrition. In Iran, “National Nutrition Improvement Program in Rural and Nomadic Women” has been developed and implemented as a NSA program. The main purpose of this study was analysis of this program using the Policy Triangle Framework. Methods This was a qualitative policy analysis study, which was conducted retrospectively. The study population included policymakers and executors at macro (Tehran Province) and micro levels (County and village) from the two involved ministries, as well as rural women in Tehran province. The collected data included the program document (N = 210), in-depth semi-structured interviews (N = 40), as well as focus group discussions (N = 8). Data was analyzed using MAXQDA 2010 software with a deductive approach. Results The findings of this study indicated that the underlying factors including social, economic and cultural status, health, structural-environmental and political are associated to the development of the program. The current program is a multi-faceted, in accordance with the existing needs, which provides opportunities to improve nutrition and community health, empower women, strengthen socio-economic status at the micro and macro levels and pave the way for other projects, by connecting the nutrition sector to agriculture. The analysis has also shown that the content of this program requires more consideration in budget and motivational measures. Although developing an NSA program based on inter-sectoral collaboration is a valuable step, it needs to be improved in the areas of sustainability, inter-sectoral collaboration, resources and facilities, monitoring and evaluation, as well as needs assessment. Conclusion The findings of the present study can be used as evidence by policymakers and planners in redesigning and implementing the program, or developing other NSA programs.